Relationship between Knowledge and training on Nurses'Skill in Managing Emergency Events among Cardiac Arrest Patients in the ICU and Emergency Room at Pelamonia Hospital, Makassa - Nusdin Nunu Nusdin; Achmad Indra Awaluddin; Darmawati Darmawati (Alta Dharma Publisher, 2020)
Emergency conditions most frequently encountered in health care settings such as hospitals, one of which is the incidence of cardiac arrest. The purpose of this study is to determine the relationship between knowledge and training with nurses' skills in managing emergency events among cardiac arrest patients in the ICU and the Emergency Room of Pelamonia Hospital. The cross-sectional study design was applied in this study. The population, as well as the sample in this study, was 40 people, this study used a total sampling technique. The value results of the study with statistical tests Fisher's Exact Test, the obtained value of p = 0.000 (? <0.05 for the knowledge variable and p = 0.008 (? <0.05) for the training variable. The conclusion of this study, there is a relationship between knowledge and training with nurses' skills in managing emergency events among cardiac arrest patients in the ICU and the Emergency Room of Pelamonia Hospital. Suggested to the health officers in particular to nurses to always improve the knowledge and always follow the latest training so that the skills on basic life support can be carried out properly